Fatal renal mucormycosis with Apophysomyces elegans in an apparently healthy male. (9th April 2021) - Rashid, Sameera; Ben Abid, Fatma; Babu, Shafiq; Christner, Martin; Alobaidly, Abdulqadir; Al Ansari, Abdulla Ali Asad; Akhtar, Mohammed
Abstract: Mucor is an angioinvasive fungus that was reported mainly in immunocompromised patients. It usually presents as rhino-orbital, pulmonary, gastrointestinal, and disseminated disease. Isolated renal mucormycosis is an extremely rare infection in immunocompetent patients and is associated with high fatality rate. Early diagnosis, prompt antifungal treatment, and surgery give the patient the best chance for cure and survival. We describe herein a case of renal zygomycosis caused by Apophysomyces elegans (A. elegans ) in an immunocompetent host. To the best of our knowledge, this is the first case of renal A. elegans to be reported from Qatar and the Middle East.